Lectotypification of Macromia pyramidalis Martin, 1907 (Odonata: Macromiidae) and its nomenclatural consequences - Kosterin, Oleg E.; Delfosse, Emmanuel (Zootaxa, 2024)
The type series of Macromia pyramidalis Martin, 1907 was for a long time suspected to be heterogeneous. The photographs of the three syntypes preserved in Muséum National d’Histoire naturelle, Paris, France (MNHN) revealed the male syntype to be consubspecific to the current Macromia pinratani vietnamica Asahina, 1996 and the two female syntypes conspecific to the current Macromia berlandi Lieftinck, 1941. The name M. pyramidalis is the oldest among those mentioned. The male syntype is designated as the lectotype of M. pyramidalis to result in somewhat less inconvenient nomenclatural consequences, which are as follows: Macromia pyramidalis pyramidalis, valid name = Macromia pinratani vietnamica, syn. nov.; Macromia pyramidalis pinratani Asahina, 1983, comb. nov.; Macromia pyramidalis, valid name = Macromia pinratani, syn. nov.